Raising the Level of Nursing Involvement in the National Precision Medicine Initiative: An Example. Issue 2 (25th May 2016) - Oruche, Ukamaka Marian; Carpenter, Janet S.; Renbarger, Jamie; Ross, Sydney E.
Abstract : PURPOSE: The Precision Medicine Initiative (PMI) goal of ushering in a new and more effective era of health care that benefits all Americans requires two critical and interdependent components: a cohort assembly of 1 million or more Americans who reflect the diversity of the United States of America and an interdisciplinary workforce that includes nursing. The purpose of this article is to provide an example of nursing involvement in PM, specifically as related to gathering biospecimens (saliva) from vulnerable, understudied adolescents with disruptive behavior disorders and their family members. SOURCE(S): First, we provide a brief description of important concepts related to PM as well as current roles of nurses in PM. Then, we share lessons learned from our feasibility study aimed at increasing the diversity of our statewide cohort assembly that has provided biospecimens for the Indiana Biobank. CONCLUSION: Nurses can definitely contribute to biobanks in support of the PMI. This article is a call to action for nurses to take their rightful place in PM.